PENGARUH KEPUASAN KERJA, KEADILAN ORGANISASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN - Agustini, Ni Luh Putu Tita Yanthi; Subudi, Made (E-Jurnal Manajemen, 2018)
The purpose of this study is to determine the effect of job satisfaction, organizational justice, and organizational commitment to employee turnover intention. This research was conducted at PT. BPR Bali Dananiaga Denpasar. The total population in this study is 45 employees, and obtained the target population which is a sample of 34 employees with probability sampling method. Data collection was done through interviews and questionnaires. Data analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that job satisfaction has a negative effect and significant employee turnover intention. These results prove that if the higher job satisfaction perceived by employees, the lower turnover intention employees. Organizational justice has a negative and significant effect on employee turnover intention. These results prove that the higher the employees feel the fairness of the organization the lower turnover intention employees. Organizational commitment has a negative and significant effect on employee turnover intention. These results prove that the higher the commitment in the company, it will be able to reduce employee turnover intention.